Health risks of vibration exposure to wheelchair users in the community - Garcia-Mendez, Yasmin (Maney Publishing, 2013)
OBJECTIVE: The purpose of this study was to evaluate whole-body vibration (WBV) exposure to wheelchair (WC) users in their communities and to determine the effect of WC frame type (folding, rigid, and suspension) in reducing WBV transmitted to the person. DESIGN: An observational case-control study of the WBV exposure levels among WC users. PARTICIPANTS: Thirty-seven WC users, with no pressure sores, 18 years old or older and able to perform independent transfers. MAIN OUTCOME MEASURES: WC users were monitored for 2 weeks to collect WBV exposure, as well as activity levels, by using custom vibration and activity data-loggers. Vibration levels were evaluated using ISO 2631-1 methods. RESULTS: All WC users who participated in this study were continuously exposed to WBV levels at the seat that were within and above the health caution zone specified by ISO 2631-1 during their day-to-day activities (0.83 ± 0.17 m/second(2), weighted root-mean-squared acceleration, for 13.07 ± 3.85 hours duration of exposure). WCs with suspension did not attenuate vibration transmitted to WC users (V = 0.180, F(8, 56) = 0.692, P = 0.697). CONCLUSIONS: WBV exposure to WC users exceeds international standards. Suspension systems need to be improved to reduce vibrations transmitted to the users.